Dried blood spot testing: a novel approach for the therapeutic drug monitoring of ziprasidone-treated patients. (June 2014) - Mercolini, Laura; Mandrioli, Roberto; Protti, Michele; Conca, Andreas; Albers, Lawrence J; Raggi, Maria Augusta
Background: A novel analytical approach, based on dried blood spot (DBS) testing, has been developed, validated and applied for the first time to the analysis of ziprasidone (ZPR) for the therapeutic drug monitoring (TDM) of schizophrenic patients. DBS represent a more feasible but reliable matrix, alternative to blood and plasma.Methods: The assays were carried out using an HPLC method with native fluorescence. Blood drops were applied to DBS cards and dried by microwaves, an internal standard solution was added to the DBS and 5-mm punches were cut out for analysis. ZPR was extracted from DBS with methanol, giving good extraction yields, precision and selectivity results.Results: The method was applied with satisfactory results to DBS samples from psychiatric patients to determine ZPR levels for therapy optimization.Conclusion: This innovative methodology provides reliable and significant TDM information, with important advantages over classical blood sampling in terms of collection, storage and processing.